Development of the small punch test platform to evaluate the embrittlement of power plant materials - Tshamano, Lavhelesani Oliet (Centre for Materials Engineering, 2018)
Life assessment of critical components and piping is performed in the electrical power plants in order to prevent structural/component failure and prolong safe operation of the equipment. In the event that these components fail, the consequences can be very costly since this may result in power supply disruptions, component replacements, environmental damages and the loss of human life. Regulations, standards and codes are designed to ensure the safe operation of the power plants. However, on their own, they are not adequate to account for aging power plants that have been in service for more than half of their originally designed lifespans, since failures have been experienced due to in-service aging mechanisms (i.e. temper embrittlement, creep, etc.) and poor engineering and maintenance practises. Mechanical, metallurgical and non-destructive techniques are used to evaluate the condition of the in-service materials in order to aid in these life assessments. The structural integrity assessments utilise material toughness properties as determined through fracture toughness testing, which requires a significant quantity of material, and is therefore cumbersome and expensive. Consequently, several other material property testing techniques are used to aid in structural integrity assessments, such as impact energy, tensile and hardness testing. Through empirical correlations, these test results are used to estimate fracture toughness properties and, consequently, the error bands are expected to be as high as 50%. Due to its small size, the small punch test (SPT) technique can be regarded as a quasi-non-destructive test, and is therefore a preferred method for determining the fracture toughness in aid of structural assessment. The SPT technique involves a compression load from the punch to a sample (ϕ8mm x 0.5mm thick) clamped between clamping and receiving dies. This study aims to develop a test rig that will be used to perform the SPT in order to quantify the level of embrittlement on the ex-service, low-pressure steam turbine material (NiCrMoV steel). The data results acquired from the SPT technique are the reaction load of the punch and the deformed displacement of the sample performed at a constant displacement rate according to CWA 15627:2007. Two SPT rigs were designed, manufactured and commissioned. These two were commissioned using FEM and tensile test results for validations. The steel was subjected to three different conditions: as received (AR), de-embrittled (DE) and hardened (HD). The three types of steel illustrated that the SPT can quantify embrittlement levels through the correlation of tensile, Charpy impact energy and fracture toughness testing.